INSTITUTIONAL ENTREPRENEURSHIP IN THE SPONSORSHIP OF COMMON TECHNOLOGICAL STANDARDS: THE CASE OF SUN MICROSYSTEMS AND JAVA. - Garud, R.; Jain, S.; Kumaraswamy, A. (Academy of Management Journal, 2002)
The institutional entrepreneurship implicit in a firm's sponsorship of its technology as a common standard is beset by several challenges. These challenges arise from a standard's property to enabl...